1985
DOI: 10.1002/jor.1100030210
|View full text |Cite
|
Sign up to set email alerts
|

Forces in the normal and abnormal hand

Abstract: An analytic model for human hand force analysis was developed through anatomical study and measurement of multiple cadaveric specimens. A method of solution was developed to determine muscle and joint force distributions under various isometric hand functions. Applications of this model to abnormal conditions include studying the effects of tendon laceration, neuromuscular weakness, and surgical restoration by tendon transfer. Limitations and further applications of the model are discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
3
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(103 citation statements)
references
References 23 publications
12
84
3
4
Order By: Relevance
“…The former result was expected (Matheson et al 1970;Pataky et al 2007a). The latter could not be predicted from Index finger anatomy: the Index finger has a radial interosseous with a greater moment arm (An et al 1983) and greater physiological cross-sectional area (An et al 1985) than the ulnar interosseous. The results could also not be predicted from the Index finger biomechanics literature.…”
Section: Discussion Strengthmentioning
confidence: 91%
“…The former result was expected (Matheson et al 1970;Pataky et al 2007a). The latter could not be predicted from Index finger anatomy: the Index finger has a radial interosseous with a greater moment arm (An et al 1983) and greater physiological cross-sectional area (An et al 1985) than the ulnar interosseous. The results could also not be predicted from the Index finger biomechanics literature.…”
Section: Discussion Strengthmentioning
confidence: 91%
“…The lunate is palmarly wedgeshaped in configuration and tends to extend under axial compression load. 24,25 Based on calculations by An et al, 26 the total force transmitted by the metacarpals to the carpal can reach values greater than 10 times the applied force on the fingers. Such forces are both the consequence of an external load being transferred along the different digital rays and the results of the action of specific muscles and ligaments necessary to achieve joint stability.…”
Section: Discussionmentioning
confidence: 99%
“…Several biomechanical studies support this assertion. An et al (55) demonstrated that the compressive force across the articular surface is much higher in the PIP and MCP joints than DIP joints during grasp (hand grip), briefcase grip, holding a glass, or opening a jar. In grasp, compression forces have been shown to rise dramatically from the IP joint of the thumb to the first MCP to the first CMC joint (56).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%